![y=(9-7x)^8, \\ y'=((9-7x)^8)'=8(9-7x)^7\cdot(9-7x)'=8(9-7x)^7\cdot \\ \cdot(9'-(7x)')=8(9-7x)^7\cdot(0-7x')=8(9-7x)^7\cdot7= \\ =56(9-7x)^7, \\ \\ y=\sqrt{9x+1}, \\ y'=(\sqrt{9x+1})'=((9x+1)^\frac{1}{2})'=\frac{1}{2}(9x+1)^{-\frac{1}{2}}\cdot(9x+1)'= \\ =\frac{1}{2(9x+1)^\frac{1}{2}}\cdot((9x)'+1')=\frac{1}{2}\cdot\frac{1}{\sqrt{9x+1}}\cdot(9x'+0)= \\ =\frac{1}{2\sqrt{9x+1}}\cdot9=\frac{9}{2\sqrt{9x+1}}, y=(9-7x)^8, \\ y'=((9-7x)^8)'=8(9-7x)^7\cdot(9-7x)'=8(9-7x)^7\cdot \\ \cdot(9'-(7x)')=8(9-7x)^7\cdot(0-7x')=8(9-7x)^7\cdot7= \\ =56(9-7x)^7, \\ \\ y=\sqrt{9x+1}, \\ y'=(\sqrt{9x+1})'=((9x+1)^\frac{1}{2})'=\frac{1}{2}(9x+1)^{-\frac{1}{2}}\cdot(9x+1)'= \\ =\frac{1}{2(9x+1)^\frac{1}{2}}\cdot((9x)'+1')=\frac{1}{2}\cdot\frac{1}{\sqrt{9x+1}}\cdot(9x'+0)= \\ =\frac{1}{2\sqrt{9x+1}}\cdot9=\frac{9}{2\sqrt{9x+1}},](https://tex.z-dn.net/?f=y%3D%289-7x%29%5E8%2C+%5C%5C+y%27%3D%28%289-7x%29%5E8%29%27%3D8%289-7x%29%5E7%5Ccdot%289-7x%29%27%3D8%289-7x%29%5E7%5Ccdot+%5C%5C+%5Ccdot%289%27-%287x%29%27%29%3D8%289-7x%29%5E7%5Ccdot%280-7x%27%29%3D8%289-7x%29%5E7%5Ccdot7%3D+%5C%5C+%3D56%289-7x%29%5E7%2C+%5C%5C+%5C%5C+y%3D%5Csqrt%7B9x%2B1%7D%2C+%5C%5C+y%27%3D%28%5Csqrt%7B9x%2B1%7D%29%27%3D%28%289x%2B1%29%5E%5Cfrac%7B1%7D%7B2%7D%29%27%3D%5Cfrac%7B1%7D%7B2%7D%289x%2B1%29%5E%7B-%5Cfrac%7B1%7D%7B2%7D%7D%5Ccdot%289x%2B1%29%27%3D+%5C%5C+%3D%5Cfrac%7B1%7D%7B2%289x%2B1%29%5E%5Cfrac%7B1%7D%7B2%7D%7D%5Ccdot%28%289x%29%27%2B1%27%29%3D%5Cfrac%7B1%7D%7B2%7D%5Ccdot%5Cfrac%7B1%7D%7B%5Csqrt%7B9x%2B1%7D%7D%5Ccdot%289x%27%2B0%29%3D+%5C%5C+%3D%5Cfrac%7B1%7D%7B2%5Csqrt%7B9x%2B1%7D%7D%5Ccdot9%3D%5Cfrac%7B9%7D%7B2%5Csqrt%7B9x%2B1%7D%7D%2C+)
![y=cos(\frac{x}{2}+\frac{\pi}{4}), \\ y'=(cos(\frac{x}{2}+\frac{\pi}{4}))'=-sin(\frac{x}{2}+\frac{\pi}{4})\cdot(\frac{x}{2}+\frac{\pi}{4})'=-sin(\frac{x}{2}+\frac{\pi}{4})\cdot\frac{1}{2}= \\ =-\frac{1}{2}sin(\frac{x}{2}+\frac{\pi}{4}), \\ \\ y=\frac{2}{5x+2}, \\ y'=(\frac{2}{5x+2})'=\frac{2'\cdot(5x+2)-2(5x+2)'}{(5x+2)^2}=\frac{0-2\cdot5}{(5x+2)^2}=-\frac{10}{(5x+2)^2}; y=cos(\frac{x}{2}+\frac{\pi}{4}), \\ y'=(cos(\frac{x}{2}+\frac{\pi}{4}))'=-sin(\frac{x}{2}+\frac{\pi}{4})\cdot(\frac{x}{2}+\frac{\pi}{4})'=-sin(\frac{x}{2}+\frac{\pi}{4})\cdot\frac{1}{2}= \\ =-\frac{1}{2}sin(\frac{x}{2}+\frac{\pi}{4}), \\ \\ y=\frac{2}{5x+2}, \\ y'=(\frac{2}{5x+2})'=\frac{2'\cdot(5x+2)-2(5x+2)'}{(5x+2)^2}=\frac{0-2\cdot5}{(5x+2)^2}=-\frac{10}{(5x+2)^2};](https://tex.z-dn.net/?f=y%3Dcos%28%5Cfrac%7Bx%7D%7B2%7D%2B%5Cfrac%7B%5Cpi%7D%7B4%7D%29%2C+%5C%5C+y%27%3D%28cos%28%5Cfrac%7Bx%7D%7B2%7D%2B%5Cfrac%7B%5Cpi%7D%7B4%7D%29%29%27%3D-sin%28%5Cfrac%7Bx%7D%7B2%7D%2B%5Cfrac%7B%5Cpi%7D%7B4%7D%29%5Ccdot%28%5Cfrac%7Bx%7D%7B2%7D%2B%5Cfrac%7B%5Cpi%7D%7B4%7D%29%27%3D-sin%28%5Cfrac%7Bx%7D%7B2%7D%2B%5Cfrac%7B%5Cpi%7D%7B4%7D%29%5Ccdot%5Cfrac%7B1%7D%7B2%7D%3D+%5C%5C+%3D-%5Cfrac%7B1%7D%7B2%7Dsin%28%5Cfrac%7Bx%7D%7B2%7D%2B%5Cfrac%7B%5Cpi%7D%7B4%7D%29%2C+%5C%5C+%5C%5C+y%3D%5Cfrac%7B2%7D%7B5x%2B2%7D%2C+%5C%5C+y%27%3D%28%5Cfrac%7B2%7D%7B5x%2B2%7D%29%27%3D%5Cfrac%7B2%27%5Ccdot%285x%2B2%29-2%285x%2B2%29%27%7D%7B%285x%2B2%29%5E2%7D%3D%5Cfrac%7B0-2%5Ccdot5%7D%7B%285x%2B2%29%5E2%7D%3D-%5Cfrac%7B10%7D%7B%285x%2B2%29%5E2%7D%3B)
0, 3x^2-3>0, \\ x^2-1>0, \\ (x+1)(x-1)>0, \\ (x+1)(x-1)=0, \\ x+1=0, x_1=-1, \\ x-1=0, x_2=1, \\ x \in(-\infty;-1)\cup(1;+\infty)" alt="f(x)=x^3-3x+7, \\ f'(x)=(x^3-3x+7)'=(x^3)'-(3x)'+7'=3x^2-3, \\ f'(x)>0, 3x^2-3>0, \\ x^2-1>0, \\ (x+1)(x-1)>0, \\ (x+1)(x-1)=0, \\ x+1=0, x_1=-1, \\ x-1=0, x_2=1, \\ x \in(-\infty;-1)\cup(1;+\infty)" align="absmiddle" class="latex-formula">